COGNITIVE LINGUISTICS APPROACH AND ITS IMPLICATION FOR LANGUAGE TEACHING (Lectio: Journal of Language and Language Teaching, 2026)
The importance of understanding the relationship between language and cognition in language teaching has become a significant challenge, particularly in developing a more relevant and effective approach for students. This study aims to analyze the application of cognitive linguistics in language learning. The approach used is qualitative with a literature review method to explore cognitive linguistic theories and their application in language teaching. The main data sources come from academic articles, books, and scientific journals published in leading international databases. Through a systematic literature review, this study identifies how cognitive linguistic theories, such as cognitive grammar, conceptual metaphors, and mental schemas, are applied in the language teaching process. The findings show that cognitive linguistics can enrich language teaching by linking language concepts with cognitive processes and students' real-world experiences. Additionally, this study reveals the challenges in integrating cognitive linguistics theories into existing language education curriculum. The drawn conclusion indicates that the application of cognitive linguistics can enhance students' language comprehension and skills, although its implementation requires deeper adjustments in teaching practices.
Keywords: Cognitive linguistics; language learning; cognitive grammar; conceptual metaphors; language education